Safety and Long-Term Outcome of Intratumoral Injection of OK432-Stimulated Dendritic Cells for Hepatocellular Carcinomas After Radiofrequency Ablation - Kitahara, Masaaki (Transl Oncol, 2020)
Dendritic cell (DC)–based immunotherapies are believed to help eradicate residual tumor cells, including hepatocellular carcinoma (HCC). Here, we assessed the safety and clinical response to OK432-stimulated monocyte-derived DCs (MoDCs) in treating HCC after radiofrequency ablation (RFA). MoDCs were derived from 30 HCC patients in the presence of interleukin-4 and granulocyte-macrophage colony stimulating factor for 5 days and then cultured for 2 more days in the medium (basic protocol) or stimulated with OK432. On day 7, DCs were harvested and percutaneously injected into HCC tumors after RFA. We observed no grade 3 or 4 National Cancer Institute Common Toxicity Criteria adverse events. Kaplan-Meier analysis indicated that patients treated with RFA + OK432-stimulated DCs transfer had longer recurrence-free survival than those treated with RFA + basic-protocol DCs (median: 24.8 vs 13.0 months; P = .003). RFA with DC infusion can enhance various tumor-associated antigen (TAA)–specific T-cell responses. Additionally, the 5-year RFS rate for patients with significantly increased TAA-specific T-cell responses was much higher than for other patients (50.0% vs. 7.7%; P = .030). Our study provides useful information for development of HCC immunotherapies (trial registration: UMIN000001701).